Attribute - Level Performance Dimensions of Airline Service Quality: A Factor Analysis Approach - Pappachan, Joemon; Koshy, Moli P. (Indian Journal of Marketing, 2014)
The airline industry is facing heavy competition in the deregulated aviation market as a consequence of the emergence of low-cost airlines offering their services at prices unmatched with their rivals' legacy models. Henceforth, it is imperial for the service providers to know the relevant facets of airline service quality attributes that are perceived by regular passengers. This paper aimed to explore the underlying dimensions of airline service quality attributes perceived by the regular passengers travelling in full service carriers. The underlying dimensions of airline service quality attributes were explored through factor analysis using principal axis factoring method with direct oblimin rotation using SPSS. Three dimensions evolved from the study, they are: Employee performance specific factors, service network (schedule) performance specific factors, and in-flight service performance (travel comfort) specific factors. There existed an overall statistical validity of the measurement model established by conducting confirmatory factor analysis with structural equation modeling using AMOS. Perceived differences in factor dimensions among passengers of different categories were compared and implications were provided for the airlines.